Matching the unmatchable. Complexity theory and quantum theory (2017)
This is a philosophical paper. It claims that there is a gap to be filled in the relationship between complexity theory (CT) and quantum theory (QT). This gap concerns two very distinct understandings of time. The paper provides the ground for filling up such gap. Indeed, most works on complexity at large focus on the macroscopic world, leaving behind the importance of the microscopic world. This paper specifies what both worlds consist of, and argues that a solid account of the world, i.e. complexity, must necessarily take into account both dimensions of reality.